2010
DOI: 10.1186/1757-5036-3-10
|View full text |Cite
|
Sign up to set email alerts
|

Combined molecular dynamics and continuum solvent studies of the pre-pore Cry4Aa trimer suggest its stability in solution and how it may form pore

Abstract: Cry4Aa toxin is one of the highly specific mosquito-larvicidal proteins produced by the bacterium Bacillus thuringiensis subspecies israelensis. It is thought to form pores in the larval midgut membrane that cause membrane leakage and subsequent insect death. Therefore, Cry4Aa and other Cry toxins have been used as efficient and safe bacterial insecticides to control the disease-carrying mosquitoes such as Aedes, Anopheles, and Culex. However, we still do not clearly understand how Cry toxins kill mosquito-lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
1
10
0
1
Order By: Relevance
“…Three mutants are located in domain I, two in domain II, and two in domain III. Among the mutants located in domain I, one mutant (V171C) is located in helix ␣-5, that corresponds to the region involved in membrane insertion according to Taveecharoenkool et al (24). Our results indicate that domains II and III of the toxin remained exposed to the solvent in the surface of the membrane and only a discrete region of domain I was inserted into the lipid bilayer.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…Three mutants are located in domain I, two in domain II, and two in domain III. Among the mutants located in domain I, one mutant (V171C) is located in helix ␣-5, that corresponds to the region involved in membrane insertion according to Taveecharoenkool et al (24). Our results indicate that domains II and III of the toxin remained exposed to the solvent in the surface of the membrane and only a discrete region of domain I was inserted into the lipid bilayer.…”
supporting
confidence: 56%
“…It is important to mention that most of the pore forming toxins, such as anthrax toxin, aerolysin, ␣-hemolysin, and CDC toxins, that kill different cell types, behave in a similar way, since only a small part of these proteins inserts into the lipid bilayer, while the rest of the protein remains outside of the membrane (23). Recently, a three-dimensional structure model of the Cry4Aa pre-pore, and the pore oligomer was presented (24). In this model the authors suggested that domains II and III of Cry4Aa toxin remain in the surface in the membrane bound oligomer and only the hairpin formed by helices ␣-4 and ␣-5 of domain I is involved in the insertion into the lipid bilayer (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that multiple polar interactions, especially a network of hydrogen bonds and ionic interactions, appeared to display a key role in the stability of oligomer assemblies to the dissociation by SDS (43). We have demonstrated previously, via combined MD and continuum solvent studies, that the Cry4Aa toxin, which is very much related to Cry4Ba, could form a stable trimer in aqueous solution, as primarily attributed to the intersubunit interactions through certain polar uncharged and charged residues in the pore-forming domain DI (44). We have also shown, via mutagenesis studies, that one highly conserved polar residue, Asn 183 , situated in DI-␣5, exerts a vital role in Cry4Ba trimer prepore formation and, therefore, larvicidal activity (13).…”
Section: Discussionmentioning
confidence: 87%
“…这可能是 α/β 体系 所携带的-22 净电荷引起 [7,26] . 就静电相互作用来看, 亚基之间的静电能是不利于稳定的, 但是溶剂化极性能 有利于稳定, 总静电能为 165.9 kcal/mol, 因此静电力并 不是 Q67 荧光素酶 α 和 β 亚基稳定结合的主要作用力.…”
Section: 检测基因的表达 是检测转录因子与目的基因启动子区unclassified